Comprehensive evaluation model of the urban low-carbon passenger transportation structure based on DPSIR. (February 2023) - Li, Xinguang; Zhan, Jun; Lv, Tong; Wang, Shen; Pan, Fuquan
Highlights: Low-carbon indicators are developed considering causality and engineering phases. A method to evaluating low-carbon passenger transportation structure was proposed. The key factors and obstacles of the development of Qingdao were revealed. Our indicator framework contributes to low-carbon urban transportation. Abstract: Optimizing urban passenger transportation structure is an effective way to promote the low-carbon development of cities. Effective evaluation is an important basis for optimization. To improve the validity of the evaluation, a dual-criteria layer evaluation model of the urban low-carbon passenger transportation structure based on the Drive-Pressure-State-Impact-Response (DPSIR) model and life cycle theory is proposed. The Decision-making Trial and Evaluation Laboratory (DEMATEL) method and the G1 method were combined to determine the subjective weight. The Criteria Importance Though Intercrieria Correlation (CRITIC) method and the Entropy method are used to determine the objective weight. The equilibrium weight, which reaches a compromise between the subjective weight and the objective weight through the idea of game theory, can be regarded as an optimal equilibrium based on the DEMATEL-G1 method and the CRITIC-Entropy method. The comprehensive value can be obtained based on the equilibrium weight. The validity of the model is verified by taking Qingdao as an example. The research results indicate that the structure of urban passenger transportation in terms of low carbon in Qingdao from 2015 to 2020 has improved significantly. The length of urban rail transit lines is the key influencing factor and the restricting factor for the optimization of urban passenger transportation structure in Qingdao. The evaluation results provide a reference basis for evaluating and optimizing the urban passenger transportation structure in large and medium-sized cities, especially in coastal and hilly cities.